Sigmoid transition approach of the central pattern generator-based controller for the snake-like robot. (16th May 2017) - Qiao, Guifang; Wen, Xiulan; Lin, Jian; Wang, Dongxia; Wei, Zhong
Snake-like robots can perform various types of locomotion in the complex environments. In this article, a novel two-layered central pattern generator-based controller is proposed for controlling snake-like robots. To adapt to rough terrain, snake-like robots can dynamically adjust their locomotion through modulating the control parameters of the central pattern generator-based controller based on the sensory feedback. When the parameters are modulated through the step function, the outputs of the central pattern generator-based controller may be unsmooth or discontinuous during the transition process. This will result in stiff and flexible impulses on the motors and gearboxes. In this article, the curvilinear continuity is used to evaluate the continuity degree of the outputs of the central pattern generator-based controller. In order to avoid the damage to the joint motors, two sigmoid transition approaches are proposed. First, a sigmoid parametric modulation method for the central pattern generator-based controller is proposed to eliminate the abrupt changes in the control signals of the joint motors. Second, a sigmoid start-up method is presented to improve the motion efficiency of the snake-like robot. The simulation results of the snake-like robot show that the outputs of the central pattern generator-based controller transit smoothly with the proposed sigmoid parametric modulation method. The snake-like robot can perform a soft start when the sigmoid start-up method is applied. The results demonstrate that the central pattern generator-based controller and the two proposed sigmoid transition approaches are effective.